2004
DOI: 10.1097/01.aog.0000139835.34168.b0
|View full text |Cite
|
Sign up to set email alerts
|

Focused Ultrasound Therapy of Vulvar Dystrophies: A Feasibility Study

Abstract: Vulvar dystrophy could be effectively treated with focused ultrasound therapy. This approach appears to be a new promising treatment method, although further studies are still needed. LEVEL OF EVIDENCE II-3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 17 publications
0
52
0
Order By: Relevance
“…In LS, the microvessels are reduced in the lower part of derma, leading to blood flow reduction and to shrinkage of the epidermis. Li and colleagues 5,8,19,20 suggest that the pathological changes of LS are predominantly caused by changes of the microvessels in the dermal layer, which results in secondary epidermal degeneration. CD34 antibody is mainly used to mark the blood vessel's intraepithelial cells , which stains the cell membrane and cytoplasm to yellow-brown color.…”
Section: Discussionmentioning
confidence: 99%
“…In LS, the microvessels are reduced in the lower part of derma, leading to blood flow reduction and to shrinkage of the epidermis. Li and colleagues 5,8,19,20 suggest that the pathological changes of LS are predominantly caused by changes of the microvessels in the dermal layer, which results in secondary epidermal degeneration. CD34 antibody is mainly used to mark the blood vessel's intraepithelial cells , which stains the cell membrane and cytoplasm to yellow-brown color.…”
Section: Discussionmentioning
confidence: 99%
“…[48] Doses of 8–30 mg daily for 4 months have been used which gave benefits both in symptoms and also induce resolution of lesions. Mechanism of action of systemic retinoids in LS particularly in genital LS is not clear; mostly, it acts by downregulation of fibroblast function.…”
Section: Systemic Therapymentioning
confidence: 99%
“…Because cells of the diseased tissues are more sensitive to heat than normal cells, lowintensity ultrasound at certain spectra can specifically damage cells of the diseased tissues while maintaining the integrity of normal anatomical structures to permit tissue repair and restore normal morphology and function. 11-13 Li C et al 14 have shown that FU can effectively damage the dermis of vulvar lesions, promote the repair and regeneration of capillaries and small blood vessels in dermis, improve the nutrition of nerve endings and maintain the integrity of local tissues and organs. Ultramicroscopic morphology confirmed that ultrasound treatment could significantly affect vascular endothelial cells and basal cells in the dermis.…”
Section: Discussionmentioning
confidence: 99%